Epidemiological and clinical characterization of community, healthcare-associated and nosocomial colonization and infection due to carbapenemase-producing Klebsiella pneumoniae and Escherichia coli in Spain - Salamanca-Rivera, Elena; Palacios-Baena, Zaira R.; Cañada, Javier E.; Moure, Zaira; Pérez-Vázquez, María; Calvo-Montes, Jorge; Martínez-Martínez, Luis; Cantón, Rafael; Ruiz Carrascoso, Guillermo; Pitart, Cristina; Navarro, Ferran; Bou, Germán; et al. (Infection, 2024)
Background Community-acquired (CA) and healthcare-associated (HCA) infections caused by carbapenemase-producing Enterobacterales (CPE) are not well characterized. The objective was to provide detailed information about the clinical and molecular epidemiological features of nosocomial, HCA and CA infections caused by carbapenemase-producing Klebsiella pneumoniae (CP-Kp) and Escherichia coli (CP-Ec). Methods A prospective cohort study was performed in 59 Spanish hospitals from February to March 2019, including the first 10 consecutive patients from whom CP-Kp or CP-Ec were isolated. Patients were stratified according to acquisition type. A multivariate analysis was performed to identify the impact of acquisition type in 30-day mortality. Results Overall, 386 patients were included (363 [94%] with CP-Kp and 23 [6%] CP-Ec); in 296 patients (76.3%), the CPE was causing an infection. Acquisition was CA in 31 (8.0%) patients, HCA in 183 (47.4%) and nosocomial in 172 (48.3%). Among patients with a HCA acquisition, 100 (54.6%) had been previously admitted to hospital and 71 (38.8%) were nursing home residents. Urinary tract infections accounted for 19/23 (82.6%), 89/130 (68.5%) and 42/143 (29.4%) of CA, HCA and nosocomial infections, respectively. Overall, 68 infections (23%) were bacteremia (8.7%, 17.7% and 30.1% of CA, HCA and nosocomial, respectively). Mortality in infections was 28% (13%, 14.6% and 42.7% of CA, HCA and nosocomial, respectively). Nosocomial bloodstream infections were associated with increased odds for mortality (adjusted OR, 4.00; 95%CI 1.21–13.19). Conclusions HCA and CA infections caused by CPE are frequent and clinically significant. This information may be useful for a better understanding of the epidemiology of CPE.